2013
DOI: 10.1111/nph.12217
|View full text |Cite
|
Sign up to set email alerts
|

The role of the potato (Solanum tuberosum) CCD8 gene in stolon and tuber development

Abstract: SummaryStrigolactones (SLs) are a class of phytohormones controlling shoot branching. In potato (Solanum tuberosum), tubers develop from underground stolons, diageotropic stems which originate from basal stem nodes. As the degree of stolon branching influences the number and size distribution of tubers, it was considered timely to investigate the effects of SL production on potato development and tuber life cycle.Transgenic potato plants were generated in which the CAROTENOID CLEAVAGE DIOXYGENASE8 (CCD8) gene,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 73 publications
4
76
0
Order By: Relevance
“…Remarkably, CCD8-RNAi tubers were less responsive to GA 3 than wild-type tubers in an in vitro sprout release assay, but responded in a similar manner to CK treatment. The authors discuss this somehow unexpected result by an interaction between SL and GA which needs to be studied in more depth (Pasare et al 2013). However, taken together, the results indicate that SL inhibited tuber bud growth and may act downstream of CK and GA (Fig.…”
Section: Hormonal Controlmentioning
confidence: 85%
See 2 more Smart Citations
“…Remarkably, CCD8-RNAi tubers were less responsive to GA 3 than wild-type tubers in an in vitro sprout release assay, but responded in a similar manner to CK treatment. The authors discuss this somehow unexpected result by an interaction between SL and GA which needs to be studied in more depth (Pasare et al 2013). However, taken together, the results indicate that SL inhibited tuber bud growth and may act downstream of CK and GA (Fig.…”
Section: Hormonal Controlmentioning
confidence: 85%
“…Application of the synthetic SL GR24 to excised tuber buds alone had no significant effect on bud growth compared to water, whereas it inhibited the sprout inducing activity of GA and CK when applied together with these hormones (Pasare et al 2013). Transgenic potato plants with RNAi-mediated silencing of the carotenoid cleavage dioxygenase 8 (CCD8), a key SL biosynthetic gene, revealed that SL are involved in the control of shoot branching and different processes during the tuber life cycle (Pasare et al 2013).…”
Section: Hormonal Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The DWARF27 (D27) gene, first characterized in rice, encodes an isomerase that acts at the initial steps of this pathway by transforming trans-b-carotene to 9-cis-b-carotene (Lin et al, 2009;Alder et al, 2012;Waters et al, 2012a). CAROTENOID CLEAVAGE DIOXYGENASE7 (CCD7) and CCD8 (HTD1/D17/ DAD3/RMS5/MAX3 and D10/DAD1/RMS1/MAX4, respectively) (Sorefan et al, 2003;Booker et al, 2005;Snowden et al, 2005;Johnson et al, 2006;Zou et al, 2006;Arite et al, 2007;Drummond et al, 2009;Pasare et al, 2013) produce carlactone, a putative intermediate compound in the pathway (Alder et al, 2012;Seto et al, 2014). The MORE AXILLARY GROWTH1 (MAX1) gene, so far identified only in Arabidopsis, encodes a cytochrome P450 monooxygenase that acts downstream of CCD7 and CCD8 (Booker et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, the buds that are initiated when the shoot apical meristem (SAM) of their mother has transitioned into the reproductive state ('A and B' buds in tulip), are able to skip this kind of dormancy (Chapter 4 and (Rees 1968)). This particular dormancy is known as paradormancy and imposed by apical dominance (Lang et al 1987 (Yao and Finlayson 2015;González-Grandío et al 2017;GomezRoldan et al 2008;Liang et al 2010;Pasare et al 2013;González-Grandío and Cubas 2014;Wu et al 2015;Hartmann et al 2011). …”
Section: What Can We Learn From Axillary Bud Outgrowth In Tulip?mentioning
confidence: 99%